PERANCANGAN DESAIN KEMASAN EKONOMI KREATIF KANG EME MENGGUNAKAN KARYA FOTOGRAFI DENGAN METODE AIDA DALAM MENINGKATKAN IDENTITAS PRODUK - Riyadh, Achyar; Sumarna, Imam Budi; Djunjunan, Abdurahman (Jurusan Seni Rupa ISBI Bandung, 2024)
The purpose of this research activity is to determine the results of the implementation of the use of packaging design using photographic media to increase product identity. The method used in the research uses qualitative methods. Coworking Space or coworking space was born in 1995 in Germany which was initiated by a company called C-Base which created a collaboration space between network members and even the general public based on technology that pays attention to technological developments making communication strategies more effective supported by the presence of social media that is not limited by space and time. Social media is a virtual place where everyone can do anything to showcase, sell, and even make electronic-based sales to get the attention (Attention) of consumers so as to present interest (Interest) not a few social media are filled with photo work, be it packaging photos or product photos as brand information. A great strength if creative economic actors utilize technology as a strengthening of the branding of their business consistently, but there are still many photographic visual works presented on social media that are not in accordance with the product packaging that is delivered indirectly will provide bad value, so in this study how to utilize photographic visual works owned by creative economic actors to be presented in packaging design in accordance with the products displayed on social media.The result of this study is that there is a positive impact of the application of packaging methods using photographic media on increasing product identity, although it has not had a significant effect, there are several other variables that influence the increase in product identity in Kang Eme Packaging.